ANALISIS STAKEHOLDER DALAM PENGELOLAAN BUMDES “SUMBER REJEKI” DESA JIWAN KECAMATAN JIWAN KABUPATEN MADIUN - M. Husni Tamrin; Liliana Rifti (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2023)
Village-owned enterprises that are advanced in management require attention to the support and participation of each of the stakeholders involved. The role of stakeholders in the management of BUMDes